2000
DOI: 10.1086/301321
|View full text |Cite
|
Sign up to set email alerts
|

ROTSE All-Sky Surveys for Variable Stars. I. Test Fields

Abstract: The ROTSE-I experiment has generated CCD photometry for the entire Northern sky in two epochs nightly since March 1998. These sky patrol data are a powerful resource for studies of astrophysical transients. As a demonstration project, we present first results of a search for periodic variable stars derived from ROTSE-I observations. Variable identification, period determination, and type classification are conducted via automatic algorithms. In a set of nine ROTSE-I sky patrol fields covering ∼2000 square degr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
176
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(180 citation statements)
references
References 14 publications
3
176
1
Order By: Relevance
“…Discovered and first identified as a DEB by the Robotic Optical Transient Search Experiment 1 (ROTSE1; Akerlof et al 2000), first reported by Diethel (2001). Later also observed by the Trans-atlantic Exoplanet Survey (TrES; Alonso et al 2004), and listed in the catalogue of variable stars in the Kepler field of view of the All Sky Automated Survey (ASAS-K; Pigulski et al 2009).…”
Section: Targetsmentioning
confidence: 99%
“…Discovered and first identified as a DEB by the Robotic Optical Transient Search Experiment 1 (ROTSE1; Akerlof et al 2000), first reported by Diethel (2001). Later also observed by the Trans-atlantic Exoplanet Survey (TrES; Alonso et al 2004), and listed in the catalogue of variable stars in the Kepler field of view of the All Sky Automated Survey (ASAS-K; Pigulski et al 2009).…”
Section: Targetsmentioning
confidence: 99%
“…The ROTSE team discovered many new variable stars, as describe by Akerlof et al (2000), and has made the data publicly available 1 . Stars from the ROTSE database were chosen, as opposed to stars from the standard catalogs of δ Scuti stars, because the ROTSE stars were readily observable at the time of year when the instrument for this study was available, and were generally fainter than other samples of δ Scuti stars, thus better suited to observation by our instrument.…”
Section: Sample Starsmentioning
confidence: 99%
“…Robotic telescopes 4 (capable of computer-controlled multiple observations) have been used for a broad range of projects, such as astrometry (Carlsberg Meridian Telescope;Helmer & Morrison 1985); photoelectric photometry of preselected targets (Fairborn Observatory; Boyd et al 1984); supernova searches (KAIT; Richmond, Treffers, & Filippenko 1993); gamma-ray burst (GRB) follow-up (ROTSE; Akerlof et al 2000;Smith et al 2002, and LOTIS;Park et al 1997Park et al , 2001); exoplanet searches (STARE; Brown & Charbonneau 1999, and Vulcan;Borucki et al 2001); and asteroid searches (TAOS; Chen 1999). The search space is usually narrow, involving specific timescales, light-curve shapes, and intensity ranges.…”
Section: Introductionmentioning
confidence: 99%
“…4 See, e.g., http://alpha.uni-sw.gwdg.de/∼hessman/MONET. capable of presenting their byproducts to the astronomical community, e.g., OGLE (e.g., Woźniak et al 2002), MACHO (Allsman & Axelrod 2001), and ROTSE (Akerlof et al 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation